Towards Digital Transformation in Administrative Inventory Control: A Web-Based System Development Study - Rakhman, Arif; Bakhar, Muhammad; Afriliana, Ida (International Journal of Science, Technology & Management, 2025)
The inventory information system currently employed by the General Administration Department remains largely manual, relying on Microsoft Office Excel. This approach results in inefficiencies, particularly in the retrieval and processing of inventory data, which tends to be slow and prone to errors. In response to these limitations, this study aims to develop a more efficient, user-friendly inventory management system that improves access to information and streamlines data and file handling. The proposed system is designed to enhance operational efficiency within administrative units, particularly the logistics sub-division, by providing accurate records of goods management activities, including procurement, inventory, and transactional processes. With the implementation of this system, it is expected that the handling of university logistics data will become faster, more reliable, and less prone to human error. Moreover, access to logistical information will be more readily available whenever required, supporting timely and informed decision-making.